Old Proverbs in New Skins – An fMRI Study on Defamiliarization - Bohrn, Isabel C.; Altmann, Ulrike; Lubrich, Oliver; Menninghaus, Winfried; Jacobs, Arthur M. (Frontiers in Psychology, 2012)
We investigated how processing fluency and defamiliarization (the art of rendering familiar notions unfamiliar) contribute to the affective and esthetic processing of reading in an event-related functional magnetic-resonance-imaging experiment. We compared the neural correlates of processing (a) familiar German proverbs, (b) unfamiliar proverbs, (c) defamiliarized variations with altered content relative to the original proverb (proverb-variants), (d) defamiliarized versions with unexpected wording but the same content as the original proverb (proverb-substitutions), and (e) non-rhetorical sentences. Here, we demonstrate that defamiliarization is an effective way of guiding attention, but that the degree of affective involvement depends on the type of defamiliarization: enhanced activation in affect-related regions (orbito-frontal cortex, medPFC) was found only if defamiliarization altered the content of the original proverb. Defamiliarization on the level of wording was associated with attention processes and error monitoring. Although proverb-variants evoked activation in affect-related regions, familiar proverbs received the highest beauty ratings.